Being Both Helpers and Victims: Health Professionals' Experiences of Working During a Natural Disaster. Issue 2 (3rd January 2017) - Hugelius, Karin; Adolfsson, Annsofie; Örtenwall, Per; Gifford, Mervyn
Abstract: Background: In November 2013, the Haiyan typhoon hit parts of the Philippines. The typhoon caused severe damage to the medical facilities and many injuries and deaths. Health professionals have a crucial role in the immediate disaster response system, but knowledge of their experiences of working during and in the immediate aftermath of a natural disaster is limited. Aim: The aim of this study was to explore health professionals' experiences of working during and in the immediate aftermath of a natural disaster. Method: Eight health professionals were interviewed five months after the disaster. The interviews were analyzed using phenomenological hermeneutic methods. Results: The main theme, being professional and survivor, described both positive and negative emotions and experiences from being both a helper, as part of the responding organization, and a victim, as part of the surviving but severely affected community. Sub-themes described feelings of strength and confidence, feelings of adjustment and acceptance, feelings of satisfaction, feelings of powerless and fear, feelings of guilt and shame, and feelings of loneliness. Conclusion: Being a health professional during a natural disaster was a multi-faceted, powerful, and ambiguous experience of being part of the response system at the same time as being a survivor of the disaster. Personal values and altruistic motives as well as social aspects and stress-coping strategies to reach a balance between acceptance and control were important elements of the experience. Based on these findings, implications for disaster training and response strategies are suggested. K Hugelius, A Adolfsson, P Örtenwall, M Gifford .Being both helpers and victims: health professionals' experiences of working during a natural disaster .Prehosp Disaster Med .2017 ;32 (2 ):117 –123 .